MiR-451, a potential prognostic biomarker and tumor suppressor for gastric cancer - Su, Zhongxue (Int J Clin Exp Pathol, 2015)
Background: The expression of microRNA-451 (miR-451) and its association with clinical pathological factors in GC remain still unclear. The purpose of this study was to investigate if miR-451 is a potential prognostic biomarker and tumor suppressor for gastric cancer. Methods: Real-time quantitative RT-PCR (qRT-PCR) was applied to detect miR-451 expression in GC cell lines and primary tumor and paired non-cancerous tissues. The association of miR-451 expression with clinicopathological factors and prognosis was statistically analyzed. Results: We found that miR-451 showed decreased expression in GC tissues and cell lines, and its down-regulation tended to be positively correlated with lymphatic metastasis, clinical staging and shorter overall survival of patients. In addition, forced expression of miR-451 in BGC-823 and MKN-45 cells did not impact on cell proliferation, but did reduce migration and invasion rates in BGC-823 cells. Conclusion: Our findings indicated that miR-451 may act as a novel prognostic marker and potential therapeutic target in human GC.